PENERAPAN MODEL PICTURE TO PICURE UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA KELAS IV SD NEGERI 006 PETONGGAN KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Yulandari, Herawati Siska; Witri, Gustimal; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of this research is still low with an average of 56.7 participants learning outcomes of fourth grade primary school students 006 Petonggan Raft Kulim District of Indragiri Hulu. whereas for completeness Minimum Criteria in schools is 70. Set of 22 learners only 3 people who achieve complete with the percentage of 13.64%. This study is a Classroom Action Research (CAR) conducted aims to Improve learning outcomes Indonesian students Elementary School fourth grade 006 Petonggan Raft Kulim District of Indragiri Hulu with the adoption of the Model Picture To Picture. Problem Formulation: Is the application of the model picture to picture can improve learning outcomes Indonesian Elementary School fourth grade students 006 Petonggan Raft Kulim District of Indragiri Hulu. This study was conducted on March 4, 2015 until March 19, 2015 with the second cycle. This research is the subject of the fourth grade students of SD Negeri 006 Petonggan Raft Kulim District of Indragiri Hulu the number of learners 22 people, consisting of 13 men and 9 women. data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes of students. Ie from initial data with an average of 56.7 with enough categories increased in the first daily test to 68.8 with enough categories. In the daily test II increased to 79.7 with both categories. From the data above, solid seen that with the application of learning methods picture to picture can improve student learning outcomes Elementary School fourth grade 006 Petonggan Raft Kulim District of Indragiri Hulu. This thesis Presenting the results obtained from the study of daily tests before treatment by an average of 56.7, an increase in UH I with an average value of 68.8 that approaches the minimum criteria of completeness. The next in the UH II learners acquire katergori Good value with an average value of 79.7 with the values obtained terbesut then Kretetia Ketuntuasan Minimum value has been reached with the good. Results 006 class IV Elementary School District of Kulim Rafts Indragiri Hulu that picture to picture learning methods can improve student learning outcomes Class IV Elementary School 006.Keywords: Learning model to picture Indonesian pictute